Domain-based constraint satisfaction approach to production volume allocation in multi-site manufacturing supply chain - Ng, Ngai Kheong. (2008)
The production volume allocation problem has traditionally been associated distinctly with resource management, inventory management, task management, etc. The solution to this problem have been challenged by the combinatorial effects resulting from simultaneous handling of various factors related to production volume allocation.